THE STRENGTH OF PHOTOCOPY EVIDENCE OF AUTHENTIC DEEDS IN JOINT PROPERTY DISPUTES - Saputri, Disti Anggun; Ratnaningsih; Naimah (JILPR Journal Indonesia Law and Policy Review, 2025)
Marriage is a physical and spiritual bond between a man and a woman as husband and wife with the aim of forming a happy family. In practice, not all marriages go according to plan, so divorce is a legal solution recognized by the state. Divorce not only affects the relationship between husband and wife but also causes disputes regarding the division of marital property. Marital property is joint property obtained during marriage and must be divided fairly after divorce. The legal process in court submits authentic evidence that has an important role in proving ownership of the division of marital property. Authentic evidence has higher legal force than other evidence so that it can provide legal certainty for the disputing parties. In addition, inconsistencies in evidence can cause a court decision to be detrimental to one of the parties because the evidence must ensure the validity of legal documents. As in dispute Number 1176 / Pdt.G / 2021 / PA.Lmj, the plaintiff submitted imitation authentic evidence in the trial process. This research method uses a normative legal research type using a case approach, a conceptual approach, and a statutory approach with a study of primary and secondary legal materials. The conclusion of this analysis is that the fake deed shown by the plaintiff does not have perfect evidentiary power because it is considered not attached to the deed itself, whereas in the Ratio legis as a reason for considering the judge's decision regarding the strength of authentic evidence, this fake can help the judge to make a fair decision based on the actual facts and provide legal certainty regarding the validity of the deed that is the object of the dispute.